Seoul virus infection acquired at private pet rat breeding facility, Germany, 2024 - Baalmann, Fabian; Hönemann, Mario; Drewes, Stephan; Eiden, Martin; Mehl, Calvin; Tappe, Dennis; Pantenburg, Birte; Bellmann, Steffi; Möller, Ingrid; Maier, Melanie; Pietsch, Corinna; Ulrich, Rainer G.; et al. (Emerging infectious diseases, 2025)
Seoul Virus Infection, Germany, 2024